Group Decision-making Dynamics and Financial Crisis - Skok Jezernik, Živa (Naše gospodarstvo/Our economy, 2014)
Standard models of economic theory are largely focused on individual decision-ma- king processes. Only in recent years have the awareness that many economic deci- sions are made by groups such as boards, committees, or families been strengthe- ned. Thus, group decision-making is becoming an increasingly important topic of economic research. The disadvantages of group decision making are most visible in periods of exceptional circumstances, such as during the financial crisis that star- ted in 2008. Given that the corporate governance of financial institutions is often identified as one of the main reasons for the current financial crisis and that the go- vernance of banks and other financial institutions is based on group decision-ma- king processes, we focus on the dynamics of group decision making and its impact on the formation and development of the financial crisis. In this paper, we present the findings of the prevailing theories from the field of social, cognitive, and experi- mental psychology and explain the differences between individual and group deci- sion making, emphasizing the theories of risky shift and groupthink. This is followed by a review of economic studies of group and individual decision making as well as am analysis of the impact of collective decision making on the formation and deve- lopment of the financial crisis.
Keywords: Financial crisis; corporate governance; group and individual decision making; banking